Continuous tracking of startled Drosophila as an alternative to the negative geotaxis climbing assay. (3rd July 2019) - Taylor, Matthew J.; Tuxworth, Richard I.
Abstract: The fruit fly, Drosophila, is commonly used to study late-onset neurodegenerative diseases due to the combination of powerful genetic tools, cheap and simple husbandry and short lifespan. One widely-used measure of disease progression is the age-dependent decline in motor performance that manifests in most Drosophila neurodegeneration models. This is usually quantified using a simple climbing assay. However, the standard climbing assay lacks sensitivity and suffers from high variability meaning large numbers of flies are needed or bespoke apparatus and software solutions. Here, we present a modification of the open-source, MATLAB-based, DART software to measure the decline in "startle response" with age. We demonstrate that the DART setup is more sensitive to the motor performance decline induced by adult-onset neuronal expression of amyloid beta (Aβ) peptides than a traditional climbing assay despite using smaller cohorts of flies. DART also has the potential to generate multiple metrics of motor behaviour during the startle response. The software requires no coding skills to operate and the required apparatus can be purchased commercially. Therefore, DART is a more useful method than the climbing assay for longitudinal assays of motor performance and will enable higher-throughput screen for genetic and pharmacological modifiers of neurodegeneration. In our proof-of-concept screen for modifiers of Aβ-dependent phenotypes, we identified that in vivo knock-down of p53 in adult neurons is neuroprotective. This supports recent work targeting p53 in vitro and demonstrates the potential for DART to be used to screen for targets that ameliorate neurodegeneration.